PEMANFAATAN TERATAI PUTIH SEBAGAI BAHAN BAKU PEMBUATAN SELULOSA MIKROKRISTALIN MENGGUNAKAN HIDROLISIS ENZIMATIK DARI RAYAP Coptotermes sp. - Yulianita Pratiwi Indah Lestari; Mi'rajunnisa; Raudatul Patimah; Rizka Mulya Miranti; Tuty Mulyani (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Microcrystalline cellulose is still imported by the Pharmaceutical Industry in Indonesia even though Indonesia has large natural resources but they have not been utilized optimally. Microcrystalline cellulose can be obtained from residue (extraction dregs) in the lotus plant extraction process, namely in the form of simplicia powder which will not be used again (organic solid waste). This research aims to obtain microcrystalline cellulose from several parts of the white lotus plant (Nymphaea nouchali Burm. F.) using the enzymatic hydrolysis method using cellulase from the termite Coptotermes sp., then the quality of the powder will be tested and compared with Avicel PH 101. Each part The white lotus is extracted, then the residue is delignified to obtain α-cellulose, then hydrolyzed with crude extract from Coptotermes sp termite cellulase. so that microcrystalline cellulose is obtained which will then be characterized and compared with the commercial version, namely Avicel® PH 101. The highest yield of microcrystalline cellulose is found in leaves with a yield of 95.3%, followed by leaf stalks 89.3%, flower stalks 75.7%, and the yield lowest in interest with a percentage of 74%. The physical characteristics in the form of color reaction, organoleptics, solubility and pH of white lotus microcrystalline cellulose powder show similarities with the comparison standard. It can be concluded that microcrystalline cellulose powder from several parts of the white lotus plant can be an alternative in obtaining cellulose raw materials from natural sources.